PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL DISCOVERY LEARNING PADA MATERI RASIO TRIGONOMETRI UNTUK SISWA KELAS X SMA/ MA - NADIA SAFHIRA; JALINUS JALINUS; SUHERMI SUHERMI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The research background is the importance of mathematics learning instrument as mathematics lesson plans which is arranged by the teacher as a professional worker in order to achieve mathematics learning goals. The available of mathematics learning instrument is limited, and does not refer to 2013’s Curriculum yet. This research is aimed to develop the mathematics learning instrument: syllabus, lesson plans, and student worksheets using the discovery learning model on ratio trigonometry subject for 10th grade students of SMA/ MA that is categorized as valid and the student worksheets is categorized as practical. This research used Research and Development (R&D) model with ADDIE procedure; analyze, design, development, implementation, and evaluation. Due to time and cost barriers, this research was only done until the development stage.  The research instruments that used in this research were learning instrument validation sheets and student response questionnaires. Syllabus, lesson plans, and student worksheets are validated by three validators and revised according to the validator’s suggestions, and then the student worksheets is tested on nine students of Class X MIA 6 of SMA Negeri 1 Pekanbaru. According to the result of validation data analysis of syllabus, lesson plans, and student worksheets, those were categorized as very valid with the average score for syllabus was 3.80, for lesson plans was 3.82, and student worksheets was 3.70. According to the result of student response questionnaires toward the student worksheets practicality on a limited trials, the student worksheets were categorized as very practical with a percentage of 89.19%. According to the result of data analysis and the discussion, it can be concluded that the syllabus, lesson plans, and student worksheets using the discovery learning model on ratio trigonometry subject were very valid, and the student worksheests were very practical and feasible to be used by 10th grade students of SMA/ MA. Key Words: Discovery Learning Model, Mathematics Learning Instrument, Ratio Trigonometry, Validity and Practicality.